Electrical analysis of c-Si/CGSe monolithic tandem solar cells by using a cell-selective light absorption scheme - Jeong, Ah Reum; Choi, Sung Bin; Kim, Won Mok; Park, Jong-Keuk; Choi, Jihye; Kim, Inho; Jeong, Jeung-hyun (NATURE PUBLISHING GROUP, 2017)
A monolithic tandem solar cell consisting of crystalline Si (c-Si)/indium tin oxide (ITO)/CuGaSe2 (CGSe) was demonstrated by stacking a CGSe solar cell on a c-Si/ITO solar cell to obtain a photovoltaic conversion efficiency of about 10%. Electrical analyses based on cell-selective light absorption were applied to individually characterize the photovoltaic performances of the top and bottom subcells. Illumination at a frequency that could be absorbed only by a targeted top or bottom subcell permitted measurement of the open-circuit voltage of the target subcell and the shunt resistance of the nontarget subcell. The cell parameters measured from each subcell were very similar to those of the corresponding single cell, confirming the validity of the suggested method. In addition, separating the light absorption intensities at the top and bottom subcells made us measure the bias-dependent photocurrent for each subcell. The series resistance of a c-Si/ITO/CGSe cell subjected to bottom-cell limiting conditions was slightly large, implying that the tunnel junction was a little resistive or slightly beyond ohmic. This analysis demonstrated that aside from producing a slightly resistive tunnel junction, our fabrication processes were successful in monolithically integrating a CGSe cell onto a c- Si/ITO cell without degrading the performances of both cells.
Keywords: GA CONTENT; BACK